Visible-light induced decarboxylative alkylation of quinoxalin-2(1H)-ones at the C3-position. Issue 27 (25th June 2019) - Xue, Wenxuan; Su, Yingpeng; Wang, Ke-Hu; Zhang, Rong; Feng, Yawei; Cao, Lindan; Huang, Dangfeng; Hu, Yulai
Abstract : 3-Alkylquinoxalin-2(1 H )-ones are synthesized via direct alkylation of quinoxalin-2(1 H )-ones at the C3 position under visible light irradiation. Abstract : A simple and efficient method for the visible light induced direct carbon alkylation of quinoxalin-2(1 H )-ones at the C3 position is described. This protocol employs cheap and readily available phenyliodine(iii ) dicarboxylates as the alkylation reagents to conduct decarboxylative radical coupling reaction with quinoxalin-2(1 H )-ones. The process exhibits excellent compatibility to functional groups and provides a convenient and selective access to various 3-alkylquinoxalin-2(1 H )-ones in good yields.